Mechanical performance of asphalt mixtures produced with cork or rubber granulates as aggregate partial substitutes - Pereira, Simão (2013)
This work comprises the study of asphalt mixtures produced with cork and rubber granulates as partial aggregate substitutes. Although these alternative materials are considered waste, they might contribute to reduce tyre-road interaction noise and therefore, to promote pavements’ sustainability. However, their incorporation into asphalt mixtures must not compromise their mechanical performance. Thus, as a first step to the subject, laboratory tests were conducted on two asphalt mixtures containing rubber or cork granulates and their performance was compared to that of a conventional mixture. Promising results were obtained for the alternative mixtures, making them ready for testing their acoustic performance.